In good company: In the future, every business might be social - Petroske, Christian (Institutional Knowledge at Singapore Management University, 2018)
It sounds like a riddle: why would Coca Cola, one of the biggest soft drinks companies in the world, be investing in a cause to empower fi ve million female entrepreneurs globally by 2020? It’s true:1 the Coca Cola Company’s initiative, called 5by20, is a forerunning example of a trend sweeping the corporate world. This trend is known by many names, the foremost of which are “shared value”, “inclusive business” or “sustainable business”. Their defi nitions can seem murky at fi rst, but these terms share a common thread. They sit at the intersection of economy and society, one that could reshape business' role in humanity's future. Their meaning holds the key to our fi rst question: why would Coca Cola sink so much into such an ambitious corporate social responsibility (CSR) goal?2